Observation of the use of the audiolingual method for increasing speaking skill in the english language learning in Sexto Grado de Educación General Básica “A” at princeton School, Located in Riobamba City, Chimborazo Province in the Academic Year September 2016- July 2017 - Novillo Orozco, María Cristina (2017)
The Audiolingual method is centred on developing the speaking skill where the teacher is the one who directs the class through modelling new structures and making students repeat and imitate them later, this process certifies the effectiveness of this method for developing students’ oral skills. This research is focused on observing how the Audiolingual method helps in the improvement of speaking skill of students at Sexto Año de Educación General Básica “A” at Princeton School, located in the city of Riobamba. The population was constituted by thirteen students and a professor. The study is exploratory, the qualitative method used was ethnographic which helped to identify and analyse the problem as it occurs in the exactly place where it occurs. The instrument used was an observation guide, which were built considering the main characteristics of the Audiolingual Method and to obtain useful information to accomplish the study objectives. Along the research, it was possible to identify that the most used activity the teacher used, are the commands, and there was not any activity which students had to communicate with each other. It was also noticed that when the teacher used some activities based on Audiolingual method she omitted many important steps; that is why the final learning objectives were not accomplished.